2015
DOI: 10.14238/pi55.5.2015.02
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in children with cancer and their normal siblings

Abstract: Background Cancer treatment in children influences the quality

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Cancer and its treatment has not only physical effects but also social and emotional effects. 2 They experience fears and worries in relation to their child's life and in relation to whether the treatment will lead to a full recovery. 3 Almost all parents have reported experiencing feelings of distress when watching their child suffer in this way.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer and its treatment has not only physical effects but also social and emotional effects. 2 They experience fears and worries in relation to their child's life and in relation to whether the treatment will lead to a full recovery. 3 Almost all parents have reported experiencing feelings of distress when watching their child suffer in this way.…”
Section: Introductionmentioning
confidence: 99%
“…The median value of quality of life of children was 77.88, with minimum value of 50.55 and maximum of 98.15. The study done by Hilda et al reported the average quality of life of children with cancer was 42.1% (Hilda et al, 2015). This research showed no significant relationship between OP and quality of life of children (p = 0.469).…”
Section: Discussionmentioning
confidence: 69%
“…According to International Association of Cancer Registries in the study by Steliarova et al hematologic cancer was the most commonly found cancer type in children worldwide, at around 36% of total cases (Steliarova et al, 2017). Now, Hilda et al reported 69.6% of hematologic cancer cases in their study taking place in Haji Adam Malik hospital Medan in year 2012 (Hilda et al, 2015). As for duration of diagnosis, most patients (32.4%) had been diagnosed with cancer for about 1 to 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation